Association of Polymorphisms of the Receptor for Advanced Glycation Endproducts Gene with Schizophrenia in a Han Chinese Population. (8th March 2017) - Fu, Jiawu; Zuo, Xiang; Yin, Jingwen; Luo, Xudong; Li, Zheng; Lin, Juda; Zhao, Bin; Ma, Guoda; Li, Keshen
Abstract : Receptor for Advanced Glycation Endproducts (RAGE) is a member of the immunoglobulin superfamily that binds diverse ligands involved in the development of inflammatory damage and diverse chronic diseases including schizophrenia. Here, three single-nucleotide polymorphisms (SNPs) (G82S, -374T/A, and -429T/C) in the RAGE gene were genotyped in 923 patients with schizophrenia and 874 healthy-matched controls in a Han Chinese population using the SNaPshot technique. Additionally, we investigated the association among aforementioned SNPs with the clinical psychotic symptoms of the patients and neurocognitive function. Our study demonstrated that the frequencies of the TC + CC genotypes and the C allele in the -429T/C polymorphism were significantly lower in the patients compared with the controls (p = 0.031 and p = 0.034, resp.). However, the significant effect disappeared when using Bonferroni correction (p = 0.0 93 and p = 0 . 102, resp.). And there were no significant differences in the genotype and allele frequencies between the patients and the controls for G82S and -374T/A polymorphisms. Additionally, the -429T/C C allele carriers had marginally higher Symbol coding scores than the subjects with the TT genotypes [p = 0.031 and p (corr) = 0.093]. Our data indicate that the RAGE -429T/C polymorphism may be associated with the susceptibility of schizophrenia.